Role of PRGF (Plasma Rich in Growth Factors) in Periodontal Regeneration - Mohit Das; Abhaya Chandra Das; Sourav Panda; Manoj Kumar; Rinkee Mohanty; Gatha Mohanty (Indian Journal of Forensic Medicine & Toxicology, 2021)
Platelet-rich-growth-factors (PRGF), a modification of fibrin glue made from autologous blood, is beingused to deliver growth factors in high concentration to sites requiring osseous grafting. Growth factorsreleased from the platelets include platelet-derived growth factor(PDGF), transforming growth factor-beta(TGF-ß), platelet-derived epidermal growth factor (PDGF), platelet-derived angiogenesis factor, insulin-likegrowth factor 1(IGF1), and platelet factor 4. These factors signal the local mesenchymal and epithelial cellsto migrate, divide, and increase collagen and matrix synthesis. Anitua et al in 2001 introduced the concept ofPRGF and since then it has been used for a variety of purposes in the field of dentistry and oral implantologyfor proper wound healing and regeneration of periodontal tissues. This review aims to give a brief ideaabout the various uses of PRGF and the possibility of utilization in the future taking into consideration manystudies that have been done. The main advantage of using PRGF is that it lacks the leukocyte content thuspreventing damage to the tissues during healing due to the acid hydrolases and proteases released from theneutrophils. It has been previously used for treating intrabony defects, to increase the implant-bone contactarea, for recession coverage etc. In other fields of medicine, it has been used to cure osteoarthritis, to treatchronic ulcers as well. Therefore, PRGF is a very effective blood concentrate with a high concentration ofgrowth factors and its use should be increased in the clinical practice.